Safety evaluation of cinacalcet: Signal mining and analysis of adverse events based on the FAERS database - Junxia Cao; Na Yang; Cheng Huang (PLoS ONE, 2025)
Objective This study utilized the FDA Adverse Event Reporting System (FAERS) to assess signals of adverse events (AEs) associated with cinacalcet, aiming to enhance its safe and rational clinical application. Methods Adverse event reports related to cinacalcet were extracted from the FAERS database from the first quarter of 2004 to the first quarter of 2025. The AE reports were categorized by Preferred Terms (PTs) and System Organ Classes (SOCs), and risk signals were analyzed using disproportionality analysis. Results Among 30,540 AE reports where cinacalcet was the primary suspect drug, females exhibited a higher reporting frequency than males (47.30% vs. 39.80%). The highest proportion of reports was observed in the 60–74 age group (23.85%). Most AEs predominantly occurred within <7 days (11.14%) or ≥60 days (26.35%) of drug administration. A total of 78 significant PT signals were detected, including known AEs such as nausea, vomiting, loss of appetite, abdominal discomfort, hypocalcemia and epigastric pain, aligning with the drug’s prescribing information. Additionally, several AEs previously undocumented in the drug’s specifications were observed, including precocious puberty, parathyroid hemorrhage, hypoproteinemia, pancreatic atrophy, monocytopenia, cardiac death and arrhythmia. Conclusion Patient evaluation should be conducted prior to the clinical use of cinacalcet, particularly for individuals with heart failure, hepatic or renal insufficiency, and hypocalcemia. Close monitoring of electrolytes and vigilance for gastrointestinal, cardiovascular, and endocrine-related AEs are recommended. Prompt interventions should be implemented in cases of adverse reactions or disease progression to prevent serious complications or deterioration.